Efficient Parallel Ray Tracing Algorithm for Electromagnetic Scattering in Inhomogeneous Plasma Using Graphic Processing Unit - Wang, Yijing; He, Xinbo; Wei, Bing (Symmetry (Basel), 2025)
This paper presents a parallel ray tracing (RT) algorithm based on a graphic processing unit (GPU) applied to electromagnetic scattering calculations in an inhomogeneous plasma to enhance the computational efficiency of the algorithm. The proposed algorithm utilizes a fourth-order Runge–Kutta method to solve the Haselgrove equation to track ray paths within the inhomogeneous plasma and implements parallel processing of the RT procedure using GPU. By independently assigning single threads to the rays originating from the vertices and the midpoints of each triangulated ray tube, a substantial number of rays are traced in parallel to reduce the algorithm runtime. The results indicate that the parallel RT algorithm based on GPU significantly enhances computation efficiency in inhomogeneous plasma while maintaining accuracy.